2022
DOI: 10.1111/jgs.17800
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term sex differences in all‐cause and infection‐specific mortality post hip fracture

Abstract: Background Mortality rates among men are double that of women in the first 2 years after hip fracture and may be related to more infections. Research has only examined differences in short‐term mortality after hip fracture. Thus, the objective was to determine if long‐term all‐cause mortality and infection‐specific mortality rates are higher in men compared to women. Methods Data come from a prospective cohort study (Baltimore Hip Studies 7th [BHS‐7]) with up to 10.2 years of follow‐up (2006–2018). The partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Our results were congruent with previous studies that have reported higher risk of post-fracture mortality among men [ 42 , 43 ]. This could be due to higher rate of pre-existing comorbidities and post-fracture infections, and lower use of pre- and post-fracture osteoporosis medications [ 42 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were congruent with previous studies that have reported higher risk of post-fracture mortality among men [ 42 , 43 ]. This could be due to higher rate of pre-existing comorbidities and post-fracture infections, and lower use of pre- and post-fracture osteoporosis medications [ 42 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were congruent with previous studies that have reported higher risk of post-fracture mortality among men [ 42 , 43 ]. This could be due to higher rate of pre-existing comorbidities and post-fracture infections, and lower use of pre- and post-fracture osteoporosis medications [ 42 , 44 ]. Additional studies are needed to understand how the usage of pre-injury medications differed across sex in patients with hip fractures in Victoria and the impact on post-fracture outcomes and mortality.…”
Section: Discussionsupporting
confidence: 93%
“…7 Prior work has consistently shown sex differences in hip fracture recovery, with men generally faring worse in functional and mortality outcomes. [8][9][10] Many hypotheses have been developed to explain the sex differences. Primarily, males have greater bone mineral density (BMD) compared to females over the lifetime, and do not experience a precipitous loss in BMD like females during menopause.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The combined underlying disease is also a susceptible cause of postoperative incisional infections. [18] The results of the study showed that having diabetes is a risk factor for postoperative incisional infection in patients with ankle fractures. Patients with diabetes often have decreased body immunity and poor body composition, and elevated blood glucose provides a good environment for bacteria to survive and reproduce.…”
Section: Discussionmentioning
confidence: 93%